2020
DOI: 10.1021/acscatal.0c03336
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Mechanics of Dynamic Surfaces: Stimulating Methods for Promoting Catalytic Resonance

Abstract: Transformational catalytic performance in rate and selectivity is obtainable through catalysts that change on the time scale of catalytic turnover frequency. In this work, dynamic catalysts are defined in the context and history of forced and passive dynamic chemical systems, with classification of unique catalyst behaviors based on temporally-relevant linear scaling parameters. The conditions leading to catalytic rate and selectivity enhancement are described as modifying the local electronic or steric enviro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(160 citation statements)
references
References 327 publications
4
156
0
Order By: Relevance
“…Section "Validity of the BEP Relationship") (Exner, 2019d(Exner, , 2020c. In addition to these and many other studies based on microkinetic considerations in the steady-state approximation (Wang et al, 2009;Holewinski and Linic, 2012;Marshall and Vaisson-Béthune, 2015;Shinagawa et al, 2015;Tao et al, 2019;Mefford et al, 2020;Tichter et al, 2020;, Dauenhauer and coworkers directly calculated the timedependent kinetics of electrochemical processes, proposing that an oscillation in the driving force may lead to an enhancement in the reaction rate compared to the steady state (Ardagh et al, 2019;Shetty et al, 2020). This is because temporal oscillations allow a single catalytic material to exhibit multiple free-energy landscapes, which promote different parts of the reaction.…”
Section: Kinetic Effects Beyond the Bep Relationshipmentioning
confidence: 99%
“…Section "Validity of the BEP Relationship") (Exner, 2019d(Exner, , 2020c. In addition to these and many other studies based on microkinetic considerations in the steady-state approximation (Wang et al, 2009;Holewinski and Linic, 2012;Marshall and Vaisson-Béthune, 2015;Shinagawa et al, 2015;Tao et al, 2019;Mefford et al, 2020;Tichter et al, 2020;, Dauenhauer and coworkers directly calculated the timedependent kinetics of electrochemical processes, proposing that an oscillation in the driving force may lead to an enhancement in the reaction rate compared to the steady state (Ardagh et al, 2019;Shetty et al, 2020). This is because temporal oscillations allow a single catalytic material to exhibit multiple free-energy landscapes, which promote different parts of the reaction.…”
Section: Kinetic Effects Beyond the Bep Relationshipmentioning
confidence: 99%
“…During dynamic catalysis, the catalytic state, or potential energy surface (PES), oscillates with a wavelength 𝜆 (or frequency 𝑓 = 1/𝜆). In this example, the rate constants are 𝑘 𝑖 = 𝑘 𝑖 [1] for time 𝛿𝑡 [1] = 𝜆/2 followed by 𝑘 𝑖 = 𝑘 𝑖 [2] for time 𝛿𝑡 [2] = 𝜆/2, as illustrated in Figure 1a. This oscillation repeats indefinitely.…”
Section: Finding Analytical Solutions For Limit Cycles In Dynamic Catalysismentioning
confidence: 99%
“…where 𝜃 * + 𝜃 A * = 1, 𝑘 𝑖 = 𝑘 𝑖 [1] for 𝑛𝜆 ≤ 𝑡 < (𝑛 + 1/2)𝜆 and 𝑘 𝑖 = 𝑘 𝑖 [2] for (𝑛 + 1/2)𝜆 ≤ 𝑡 < (𝑛 + 1)𝜆, with the initial condition 𝜃 𝐴 * (𝑡 = 0) = 0. After forward integration of hundreds of wavelengths, the fractional coverage of A* converges to a periodic limit cycle where (eq.…”
Section: Finding Analytical Solutions For Limit Cycles In Dynamic Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was further predicted that oscillations need to be in approximate resonance with the surface reactions to achieve reaction enhancements. [9][10][11][12] DFT calculations by Shetty et al revealed electric field-dependent linear scaling relationships of adsorbates on metal surfaces imperative for the understanding of dynamic catalytic processes. 13 Cycling between a potential suitable for the non-Faradaic dehydration of FA to surfaceadsorbed CO and the Faradaic oxidative desorption to form CO 2 enhanced the activity by a factor of up to around 20 at frequencies of 100 Hz, 14 consistent with promotional effect observed by Adžić et al earlier.…”
Section: Introductionmentioning
confidence: 99%